PENENTU CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA FAST FASHION BRAND INTERNASIONAL DI KOTA BATAM - Candy (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
In the current era of globalization, the business world is proliferating, especially in the fashion business, so that the level of competition that occurs in various countries is getting higher. The high level of competition causes entrepreneurs to have to compete fairly to maintain positive perceptions of products and brands in the minds of consumers. That way, consumers will be loyal and not easily influenced by other brands in the market. The purpose of this study was to determine whether perceived quality, brand image, and promotion partially and simultaneously affect customer satisfaction and customer loyalty to international fast fashion brands in Batam City. Data were collected from 416 respondents of H&M and Uniqlo stores in the Batam City area. The results of data analysis show that brand image and customer satisfaction have a significant positive effect on customer loyalty, while perceived quality and promotion have no significant effect on customer loyalty. Promotion does not have a significant effect on customer satisfaction. Brand image and perceived quality have a significant positive effect on customer satisfaction.